Bonds of affection : civic charity and the making of America--Winthrop, Jefferson, and Lincoln - Holland, Matthew Scott, 1966- (Religion and politics series (Georgetown University), 2007)
Notions of Christian love, or charity, strongly shaped the political thought of John Winthrop, Thomas Jefferson, and Abraham Lincoln as each presided over a foundational moment in the development of American democracy. Matthew Holland examines how each figure interpreted and appropriated charity, revealing both the problems and possibilities of making it a political ideal. Holland first looks at early American literature and seminal speeches by Winthrop to show how the Puritan theology of this famed 17th century governor of the Massachusetts Colony (he who first envisioned America as a City up.